Feasibility of a mobile feedback system for gait retraining in people with lower limb loss—A technical note. (January 2019) - Fiedler, Goeran; Kutina, Krista
Gait retraining in people with musculoskeletal and/or neurological impairments requires sustained dedicated efforts by the patient and the rehabilitation therapist. Various technical approaches have been proposed and utilized to improve the effectiveness of training interventions. Among the most promising approaches is the provision of real-time feedback information to the patient, which has been used with success on treadmill-based interventions in the past. We are describing a mobile visual feedback system that is intended to work in the user's everyday-life environment. The data are captured by a small mobile load cell, processed in a wearable computer, and displayed to the user via smart-glasses. Preliminary testing of the initially selected feedback variable stance/step ratio (i.e., the duration of a step's stance phase in relation to the overall step's duration) confirmed that data quality is sufficient for purposes of generating feedback information and that the chosen variable is responsive to changes in gait symmetry. The presented work may inform future studies and developments on the topic of mobile visual feedback for gait rehabilitation.